Analisis Yuridis Pembakaran dan Penenggelaman Kapal Ikan Asing Dikaitkan dengan Asas Praduga Tidak Bersalah - Idil Nurmai Akbar; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In the context of law enforcement at sea should the effort or action to maintain and oversee compliancewith the provisions in force in the Indonesian National Jurisdiction Sea. Government of the Republic ofIndonesia in an effort to combat Illegal fishing by reference to the statutory provision fishery has made the actof burning and sinking of the fishing vessel or a foreign flag. drown 6 (six) foreign fishing vessels (KIA) inVietnamese waters illegally flagged Batam, Riau Islands Province, on October 31, 2015. The six ships areevidence that is still in the process of investigation or do not have permanent legal force (inkracht), but haveearned the determination of the Chairman of the Batam District Court to be destroyed. It is the intention thatthe deterrent effect of the perpetrator. This paper is to analyze whether the provisions of the act of burning andsinking of the fishing vessel or a foreign flag has been in accordance with the legislation in force in IndonesiaThe purpose of this journal as follows: First, to determine how the analysis of juridical burning andsinking of the foreign fishing associated with the presumption of innocence, second, whether the burning andsinking of the foreign fishing contrary to the presumption of innocence, Third, what action should be taken incracking down on foreign-flagged fishing vessels that enter into the Territory of the Republic of Indonesia inaddition to the management of fisheries burning efforts and drownings. This type of research of this thesis is anormative legal research, or should we say doctrinal legal research.From the research problem, there are three main things that concluded, first, act of burning or sinkingof the foreign fishing carried out by the investigator based on the rule of law, namely Law No. 45 of 2009 on theAmendment of Act No. 31 of 2004 on Fisheries are still ditahap investigation are inconsistent with thepresumption of innocence, and can not be said to be in accordance with the Criminal Procedure Code.Criminal Procedure Code does not authorize the destruction of evidence in the investigation ditahap. As well asthe supervisory authority regulated fishery regulated by Article 66 C Fisheries Law can not do the provisions ofArticle 76A Fisheries Act and Article 45 of the Criminal Procedure Code. Second, the sinking of the foreignfishing contrary to the presumption of innocence and the foundation of motivation Criminal Code, namelyPlatform Philosophical (Pancasila), Platform Constitutional (Constitution of the Republic of Indonesia Year1945) and the Law on Judicial Power, as well as the operational foundation (MPR No. IV / 1978), Third, otheractions carried out in addition to the act of burning and / or sinking of the foreign fishing vessels, namely theforeign fishing vessel seized by the state. The vessels are seized by the state to be auctioned or can be donatedfor social purposes or in particular can be submitted to business groups of fishermen and/or cooperativefisheries.Key words: law enforcement, evidence, criminal acts fisheries